OS SIGNIFICADOS E SENTIDOS DA RELAÇÃO ENTRE O MATRIMÔNIO E O PATRIMÔNIO MEDIADA PELO CASAMENTO NO SISTEMA CAPITALISTA - Rebeca dos Santos Moreira Soares (2022)
Why do we say matrimony, a word with a female meaning, to wedding and patrimony, which its roots have male meanings, to address goods and heritage? We deepen this investigation in the seek of understanding if this relation presented in the language is also existent in the social practice that takes part of the of the conscience of the authors in society, especially women who get married. For this, we based on the Socio-Historical Psychology Theory and elements of the Dialectical Historical Materialism. This way, we went through the History of Marriage, since the monogamic one along with the history of private property, passing on the bounds of feudal families, which were given, basically, due to political and economic alliance and also for the family and domestic economy; until the history of Brazilian marriage, which, despite having the patriarchal predominance, gathers a diverse history. Therefore, we comprehend that the State, family, Church, art and education institutions measure the matrimonial culture, either changing or conservating its aspects to conditionate ideological determiners. This way, in the historical process, we were able to identify that many women found themselves in disadvantaged regarding the matrimony, due to, traditionally, have attributed to them the domestic occupation, like reproduction and taking care of the house, and the marginalization regarding the world of work, with low payments and/or the difficulties of being employed, among other conditions. Marriage that has become, to some women, a source of surviving or even the guarantee of staying in certain social class, receives another meaning and sense in modern life, when it becomes a choice due to affinity. However, we ask ourselves if the patrimonial issue, that remains imbricated to the marriage, takes part of the conscience of those who are willing to get married. That is, what they know about the culture that motivates the action of getting married and its implication to the economy. In order to answer this, we interrogated some women about the conscience they have about their marriage patrimony. We did, then, two interviews, in which only one was chosen to be developed with the Graphic Analysis of the Speech technic. Keywords: Social-Historical Psychology. Dialectical Historical Materialism. Graphic Analysis of the Speech. Matrimony. Patrimony.